Resiliensi dan Expressive Writing di Media Sosial pada Ibu Penyintas Covid-19 - Isnatul Ismi (Psychological Journal: Science and Practice, 2023)
The sudden onset of a pandemic created a global crisis. To deal with crises is necessary to have the ability to deal with stress and adaptation in mothers who are being confirmed with Covid-19 to achieve resilience. One is by writing about their experience when they were infected on social media. Focus on the problems deep in this study, were resilience and expressive writing. The aim of this study is to reveal the resilience experiences of mothers when infected with Covid-19 who write about their condition on social media during the treatment period. The approach used is qualitative research to reveal a subjective meaning. The qualitative approach used is Interpretative Phenomenological Analysis (IPA). The research subjects are five mothers who wrote about their experiences when they were infected with Covid-19 on social media during their treatment period. Subject selection was carried out by purposive sampling technique. The five subjects wrote down their experiences during the series infected with Covid-19 to the recovery stage in the range of mid-December 2020 to the end of March 2021. The research was carried out from September 2022- October 2022 using the results of interviews and deep qualitative documents in the form of writing on the subject’s social media that was uploaded when infected with Covid-19. The data obtained were then analyzed and categorized into themes. The results of this study indicate that the five subjects have three sources of resilience, namely, I can, I have, and I am, which are seen in each phase towards resilience.